Stock Market Anomalies: A Test of Calendar Effect in the Bombay Stock Exchange (BSE) - Chandra, Abhijeet (Indian Journal of Finance, 2011)
Various seasonal patterns in returns have been found in the stock markets across the world. These patterns often referred to as anomalies, can be seasonal. This study examines whether calendar anomalies exist in the stock returns in the Bombay Stock Exchange (BSE). It investigates two types of calendar anomalies such as the turn-of-the-month effect and the time-of-the-month effect in returns in one of the leading stock exchanges of India. Data pertaining to the ten-year period of 1998-2007 has been used for testing the two types of calendar anomalies. Results reveal that the turn-of-the-month effect and the time-of-the-month effect have significantly existed in BSE Sensex returns. Returns in the first few days of the month are found to be positively significant compared to the remaining days of the month. Different time segments of a month, however, witness significantly varying returns. The evidence of this study strongly supports the existence of calendar effects in the returns of the BSE-Sensex.